2008
DOI: 10.1021/ac8004023
|View full text |Cite
|
Sign up to set email alerts
|

Online Coupling of Gas Chromatography to Nuclear Magnetic Resonance Spectroscopy: Method for the Analysis of Volatile Stereoisomers

Abstract: The identification of volatile cis/trans-stereoisomers was accomplished by employing a hyphenated GC-NMR system. The chromatographic and spectroscopic conditions were optimized with respect to the (1)H NMR detection. A special processing technique was developed to handle the recorded NMR spectra in the gas phase with very low sample amounts. The processed stopped-flow (1)H NMR spectra of the investigated chromatographic peaks unequivocally revealed the structure of the corresponding compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Fifteen micrograms (∼52 nmol) of oxypeucedanin (22 μg of oxypeucedanin hydrate, ∼72 nmol) in the 1.5 μL detection cell were sufficient to obtain an unambiguous 1 H NMR spectrum in about 2 min 20 s. This technique reduces the required sample quantity by a factor of up to 15 in comparison to a 5 mm tube in a conventional commercial probe. It is for this reason that the microcoil 1 H NMR technique proves useful with mass-limited samples and as a detector in capillary separations, as often demonstrated by our group [27][28][29][30] and several other very active European groups [31][32][33][34][35][36]. Moreover, our results confirmed that disk diffusion is a reliable, easy and inexpensive semi-quantitative susceptibility testing method that is sufficiently sensitive and ideally suited for preliminary investigations on the nano-to microscale.…”
Section: Resultssupporting
confidence: 80%
“…Fifteen micrograms (∼52 nmol) of oxypeucedanin (22 μg of oxypeucedanin hydrate, ∼72 nmol) in the 1.5 μL detection cell were sufficient to obtain an unambiguous 1 H NMR spectrum in about 2 min 20 s. This technique reduces the required sample quantity by a factor of up to 15 in comparison to a 5 mm tube in a conventional commercial probe. It is for this reason that the microcoil 1 H NMR technique proves useful with mass-limited samples and as a detector in capillary separations, as often demonstrated by our group [27][28][29][30] and several other very active European groups [31][32][33][34][35][36]. Moreover, our results confirmed that disk diffusion is a reliable, easy and inexpensive semi-quantitative susceptibility testing method that is sufficiently sensitive and ideally suited for preliminary investigations on the nano-to microscale.…”
Section: Resultssupporting
confidence: 80%
“…Considerable progress towards overcoming its relative lack of sensitivity has been achieved using microcells for the optimum use of available samples and computers to improve signal-to-noise ratio (Milazzo, Petrakis & Brown, 1968). With the aid of stronger magnets and the newly developed microprobes, the first online GC-NMR spectra was recorded recently (Grynbaum et al, 2007;Kühnle et al, 2008). These experiments revealed the high potential of this technique, but it was also shown that the peaks in the GC separation elute up to 10 min, so that the advantage of the high separation performance of GC was lost in the experiment.…”
Section: Gas Chromatography-nuclear Magnetic Resonance Spectroscopy (mentioning
confidence: 99%
“…It is suggested that the use of a transfer capillary being heated by a bifilar coil constructed from zero-susceptibility wire in combination with a strong magnetic field may solve overcome this problem (Grynbaum et al, 2007). Using stopped-flow measurements, very low sample amounts (~ 100-300 μg at 400 MHz), the potential applications of the hyphenation of high performance capillary GC to microprobe 1H NMR detection with the help of a spectra database has been demonstrated and an identification of stereoisomers in a complex mixture has been achieved (Kühnle et al, 2008). However, nanograms of volatile small compounds such as cockroach sex pheromones, mosquito attractants as well as a model compound geranyl acetate, which were prepared with an off-line GC, have already been investigated successfully using 1 H and COSY NMR (Nojima et al, 2011).…”
Section: Gas Chromatography-nuclear Magnetic Resonance Spectroscopy (mentioning
confidence: 99%
“…1,15 In one of their applications they isolated 8.6 lg geraniol from a complex essential oil matrix using MDGC and recorded remarkable 1 with a 800 MHz NMR spectrometer equipped with a cryoprobe within an acquisition time of 1 hr. 15 The second direct approach was published also quite recently and demonstrated the feasibility of an online coupling of gas chromatography and NMR spectroscopy 16,17 based on earlier reports of the direct combination of packed column and NMR instrumentation. 18,19 In a recent work, the successful capillary gas chromatographic separation and online identification of the stereoisomers of E,Z-2-pentene and of E,Z-2-hexene using a Chirasil-b-Dex stationary phase and a 400 MHz NMR spectrometer equipped with a custom-built, double resonant solenoidal microprobe was described.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In a recent work, the successful capillary gas chromatographic separation and online identification of the stereoisomers of E,Z-2-pentene and of E,Z-2-hexene using a Chirasil-b-Dex stationary phase and a 400 MHz NMR spectrometer equipped with a custom-built, double resonant solenoidal microprobe was described. 17 Both methods benefit from newer developments in the field of NMR such as microprobes 16,17,20,21 or cryoprobes [22][23][24][25] and stronger magnets, which dramatically improved the sensitivity of the relatively insensitive spectroscopic method so that the largest sample amounts, which can be separated by capillary GC are getting closer to the detection limit of NMR spectroscopy. Thus it is to be expected that many applications using a combined method of GC and NMR (offline as well as online) will emerge in the future especially if a high purity isolation is required for an unequivocal identification.…”
Section: Introductionmentioning
confidence: 99%